The problem of moisture content in historical buildings based on a classicist tenement house at 14a, Śląska Street in Gubin - Michalak, Bartosz; Graczyk, Oliwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Diagnostics and mitigation of excessive moisture effects are some of the most frequent problems in historical buildings. In this article, an attempt was made to measure the moisture content of construction elements in the historical tenement house in Gubin. It is the largest town in the Krosno Poviat, in the area of the Lubuskie Voivodeship.
Keywords: moisture content; drying; capillary action; building diagnostics; Gubin